2010
DOI: 10.1152/jn.01068.2009
|View full text |Cite
|
Sign up to set email alerts
|

Confidence-Related Decision Making

Abstract: Neurons have been recorded that reflect in their firing rates the confidence in a decision. Here we show how this could arise as an emergent property in an integrate-and-fire attractor network model of decision making. The attractor network has populations of neurons that respond to each of the possible choices, each biased by the evidence for that choice, and there is competition between the attractor states until one population wins the competition and finishes with high firing that represents the decision. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 32 publications
4
90
0
Order By: Relevance
“…Another is to consider the process as a mechanism with different levels of explanation, in the following way. We can now understand brain processing from the level of ion channels in neurons, through neuronal biophysics, to neuronal firing, through the computations performed by populations of neurons, and how their activity is reflected by functional neuroimaging, to behavioural and cognitive effects [Rolls 2008b, Rolls & Deco 2010, Rolls 2012c]. Activity at any one level can be used to understand activity at the next.…”
Section: The Mind-brain Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Another is to consider the process as a mechanism with different levels of explanation, in the following way. We can now understand brain processing from the level of ion channels in neurons, through neuronal biophysics, to neuronal firing, through the computations performed by populations of neurons, and how their activity is reflected by functional neuroimaging, to behavioural and cognitive effects [Rolls 2008b, Rolls & Deco 2010, Rolls 2012c]. Activity at any one level can be used to understand activity at the next.…”
Section: The Mind-brain Problemmentioning
confidence: 99%
“…These functions include many aspects of perception including visual face and object recognition, and taste, olfactory and related processing; short-term memory; long-term memory; attention; emotion; and decision-making [Rolls 2008b], [Rolls & Deco 2010], [Rolls 2012c[Rolls , 2014[Rolls , 2010a[Rolls , 2012b. Predictions made at one level can be tested at another.…”
Section: The Mind-brain Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain then decides on the type of behaviour to be displayed based on permutations and combinations of these coded information for a particular situation in both reward and punishment circuits and finally giving way to the stronger signal. This hypothesis finds support from the 'integrate-and-fire attractor network model' which has been electro-physiologically tested and elaborately discussed by Insabato et al [18]. The model suggests that there are populations of neurons in an attractor network which respond to each of the possible choices, biased by evidence for the choice.…”
Section: Dynamics Of the Realms Governs Ensuing Behaviourmentioning
confidence: 72%
“…Similarly, Schacter et al [51] in their constructive episodic simulation hypothesis propose that episodic memory supports the construction of predictive future events. Szpunar and Schacter further observed that increased plausibility of the future event was associated with rewarding (positive) or punishing (negative) emotional events [52]. Based on the integrateand-fire-attractor network model of [53] it may very well be proposed that neural networks of both the reward and punishment realms related to an event may be simultaneously activated and the network generating stronger potentials determines whether the ensuing behaviour is to obtain a reward or avert a punishment.…”
Section: Physiological State Of the Brain Can Influence Cognitive Promentioning
confidence: 99%